1993
DOI: 10.1016/s0022-5347(17)36465-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Partial Nephrectomy in the Pig Model

Abstract: In an effort to further evaluate the potential application of laparoscopy to urologic surgery, we explored the feasibility of using this minimally invasive approach for performing a partial nephrectomy. Nine female pigs underwent laparoscopic partial nephrectomy (LPN) utilizing a plastic cable tie (15 mm. x 4 mm. x 1 mm.) to achieve renal ischemia and an Argon Beam Coagulator probe (ABC) (Birtcher Medical Systems) to fulgurate the transected surface. Six weeks after LPN, 6 pigs underwent creatinine clearance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(48 citation statements)
references
References 2 publications
0
43
0
5
Order By: Relevance
“…[1][2][3][4] During critical portions of the procedure, arterial clamping is routinely necessary to provide a relatively bloodless field for tumor dissection and to minimize intraoperative blood loss. However, the potential for ischemic damage to the remaining renal parenchyma remains a concern.…”
mentioning
confidence: 99%
“…[1][2][3][4] During critical portions of the procedure, arterial clamping is routinely necessary to provide a relatively bloodless field for tumor dissection and to minimize intraoperative blood loss. However, the potential for ischemic damage to the remaining renal parenchyma remains a concern.…”
mentioning
confidence: 99%
“…The double loop tourniquet technique consists of two U-loop strips of umbilical tape extending from a 17 Fr plastic sheath described by Gill et al [45] in a single LPN. McDougall et al [2] and Caddedu et al [46] have reported the use of a plastic cable tie for LPN in a pig model [2]. Compression with pledgeted sutures [47] and an Endoloop [48] have also been reported in pigs.…”
Section: Parenchymal Compressionmentioning
confidence: 99%
“…Since the introduction of laparoscopic nephrectomy by Clayman in 1991 22 and the description of laparoscopic partial nephrectomy by McDougall in 1993, 21 minimally-invasive nephron-sparing renal surgery has essentially become the new standard of care for small renal masses. A natural extension of this technology has been the recent expansion of robotic surgery in this field.…”
Section: Robot-assisted Partial Nephrectomymentioning
confidence: 99%